Cervical Mesonephric Adenocarcinoma Treated with Neoadjuvant Chemotherapy: A Case Report and a Literature Review - Hiroaki Ishida; Megumi Manrai; Hiroki Egashira; Mizuki Nonaka; Nobuyuki Hiruta; Reiko Watanabe; Akiko Takashima (Diseases)
Introduction: Cervical mesonephric ductal adenocarcinoma (MA) is an HPV-independent adenocarcinoma that occurs in middle-aged women. MA originates from remnants of the Wolffian duct that usually regress in females once the induction of sex differentiation is activated. MA is a rare disease that accounts for less than 1% of all cervical adenocarcinomas. Clinical Case: We report a case of MA in which abdominal radical hysterectomy (ARH) was performed after neoadjuvant chemotherapy (NAC). The patient was a 66-year-old woman with abnormal genital bleeding. A colposcopy examination revealed macroscopic invasive cancer. A pelvic MRI scan revealed a 53 × 26 mm tumor in the cervix, and the histological diagnosis of the cervix was endometrioid carcinoma, with the diagnosis being cervical adenocarcinoma cT1b3N0M0. One course of NAC with paclitaxel-carboplatin (PC) was administered to shrink the tumor and stop the bleeding, and ARH was performed. Postoperative histopathological diagnosis was MA. The surgical margins of the resected specimen were negative, and NAC had been effective, so the patient underwent five courses of PC therapy after surgery. There has been no recurrence 12 months after surgery. Conclusions: There is no established standard treatment, but there are reports that PC therapy is effective. It is necessary to search for effective treatments by following up and accumulating further cases.